The Development of a Fuzzy Model and Usability Test of a Recommended Interface Design for Mobile Phones for Elderly Users - Polnigongit, Weerapong; Chanwimalueng, Waiwit; Fitzgerald, Sandey (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Although mobile phone application developers aim to design software to be user-friendly, elderly users report having problems with flexible user interfaces. The purpose of this study was to examine a range of flexible user interface designs for mobile phones with the aim of locating and addressing the limitations reported by elderly users. Accordingly, a fuzzy model drawing on a range of variables was developed from an age/vision impaired related data set for the development of a variety of basic design elements for user interfaces. The model was tested to assess the preciseness and accuracy of its functions, achieving a Mean Absolute Error (MAE) close to 0 and an Effectiveness Index (EI) close to 1, giving the model a high value for effectiveness. A subsequent usability test of the generated design interfaces using four types of mobile phones (18 screens in all) was conducted among 25 elderly users with vision impairment. The findings showed that the size and shape of both numeric and function buttons was a significant factor in assessing phone usability both for communication and for social media use, as was text and number size, although, significantly, the latter was qualified by screen size. Recommended numeric and dial function button sizes are 15.6mm and 16.2 mm, respectively. Likewise, recommended text and numbers sizes are 14 and 25 points, respectively. Furthermore, square-shaped buttons with rounded-edge buttons are the most suitable for elderly users, as is a background in a light shade, with texts and icons in dark colors. The model demonstrates that it is possible to design user interfaces with particular groups in mind such as the elderly and vision-impaired, in order to enhance mobile phone usability for these groups.